Analysis of the Proof of Gratuity as a Criminal Act of Corruption in Criminal Justice - Nurfathiana F; Subekti Subekti; Dudik Djaja Sidarta (PT. Anagata Sembagi Education, 2026)
This article examines the construction of proof of gratification as a form of corruption crime within the Indonesian criminal law system, particularly concerning the application of reverse proof as regulated in Law No. 31 of 1999 jo. Law No. 20 of 2001. This study uses a normative juridical method with a statutory approach, a conceptual approach, and jurisprudence review. The analysis results show that proof of gratification contains a juridical dilemma between the effectiveness of eradicating corruption and the protection of the presumption of innocence principle. Article 12B creates a shift in the burden of proof, which is normatively recognized by the Constitutional Court, but its implementation still raises issues of legal uncertainty and inconsistency in interpreting the elements of positional relationship and the intention of acceptance. The mechanism for reporting gratuities through the KPK essentially provides legal protection, but its effectiveness depends on the compliance of public officials and the capacity for oversight. This study emphasizes the need to strengthen regulations, harmonize jurisprudence, and provide technical guidelines for evidence to ensure a balance between the effectiveness of law enforcement and the protection of defendants' constitutional rights.